Dynamic Changes in High‐Sensitivity Cardiac Troponin I Are Associated with Dynamic Changes in Sum Absolute QRST Integral on Surface Electrocardiogram in Acute Decompensated Heart Failure - Tereshchenko, Larisa G. (Ann Noninvasive Electrocardiol, 2016)
BACKGROUND: A three‐dimensional electrocardiographic (ECG) metric, the sum absolute QRST integral (SAI QRST), predicts ventricular arrhythmias in heart failure (HF) patients with implantable cardioverter defibrillator and mechanical response to cardiac resynchronization therapy. We hypothesized that there is an association between patient‐specific changes in SAI QRST and myocardial injury as measured by high‐sensitivity troponin I (hsTnI). METHODS: Sum absolute integral QRST on resting 12‐lead ECG and hsTnI were measured simultaneously, every 3 hours, and during 12‐hour observation period in a prospective cohort of emergency department patients (n = 398; mean age 57.8 ± 13.2 years; 54% female, 64% black), diagnosed with acute coronary syndrome (ACS, n = 28), acutely decompensated HF (acute decompensated heart failure, n = 35), cardiac non‐ACS (n = 19), or noncardiac condition (n = 316). Random‐effects linear regression analysis assessed the association of SAI QRST and myocardial injury, with adjustment for demographics (age, sex, race), prevalent cardiovascular disease (myocardial infarction, history of revascularization, stroke, and HF), risk factors (diabetes, smoking, hypercholesterolemia, hypertension, and cocaine use), and left bundle branch block. RESULTS: Within the entire cohort, SAI QRST decreased by 3 (95%CI −5 to −1) mV*ms every 3 hours. A 10‐fold increase in hsTnI was associated with a 7.7 (0.6–14.9) mV*ms increase in SAI QRST. In the subgroup of acutely decompensated HF patients (n = 35), a 10‐fold increase in hsTnI was associated with a 61.0 (5.9–116.1) mV*ms increase in SAI QRST. CONCLUSION: Patient‐specific time‐varying changes in the surface ECG scalar measure of global electrical heterogeneity, as measured by SAI QRST, and in myocardial injury as measured by hsTnI, are independently and directly associated with each other, likely reflecting a common underlying mechanism.